Management and Outcomes of Male Breast Cancer in Zaria, Nigeria - Adamu Ahmed; Yahaya Ukwenya; Adamu Abdullahi; Iliyasu Muhammad (International Journal of Breast Cancer)
Male breast cancer is an uncommon disease accounting for only 1% of all breast cancers. We present the evaluation, treatment and outcome of male patients seen with breast cancer in our institution. Male patients that had histological diagnosis of breast cancer from 2001 to 2010 were retrospectively evaluated. After evaluation patients were treated with modified radical mastectomy. Combination chemotherapy was given to patients with positive axillary lymph nodes. Radiotherapy and hormonal therapy were also employed. There were 57 male patients with breast cancer which accounted for 9% of all breast cancers seen during the study period. Their mean age was 59 ± 2.3 years. The mean tumor diameter was 13 ± 2.5 cm. Fifty three (93%) patients presented with advanced disease including 15 with distant metastasis. Four patients with stage II disease were treated with modified radical mastectomy, chemotherapy and tamoxifen. Of the 30 patients with sage III disease that had modified radical mastectomy, complete axillary clearance and tumor free margins were achieved in 25. Overall 21 (36.8%) patients were tumor free at one year. Overall 5-year survival was 22.8%. In conclusion, male patients with breast cancer present with advanced disease which is associated with poor outcome of treatment.